Distinct xylem responses to acute vs prolonged drought in pine trees. (24th January 2020) - Guérin, Marceau; von Arx, Georg; Martin-Benito, Dario; Andreu-Hayles, Laia; Griffin, Kevin L; McDowell, Nate G; Pockman, William; Gentine, Pierre
Abstract: Increasing dryness challenges trees' ability to maintain water transport to the leaves. Most plant hydraulics models use a static xylem response to water stress. Yet, in reality, lower soil moisture and warmer temperatures during growing seasons feed back onto xylem development. In turn, adjustments to water stress in the newly built xylem influence future physiological responses to droughts. In this study, we investigate the annual variation of anatomical traits in branch xylem in response to different soil and atmospheric moisture conditions and tree stress levels, as indicated by seasonal predawn leaf water potential (ΨL, pd ). We used a 6-year field experiment in southwestern USA with three soil water treatments applied to Pinus edulis Engelm trees—ambient, drought (45% rain reduction) and irrigation (15–35% annual water addition). All trees were also subject to a natural 1-year acute drought (soil and atmospheric) that occurred during the experiment. The irrigated trees showed only moderate changes in anatomy-derived hydraulic traits compared with the ambient trees, suggesting a generally stable, well-balanced xylem structure under unstressed conditions. The artificial prolonged soil drought increased hydraulic efficiency but lowered xylem construction costs and decreased tracheid implosion safety (( t/b ) 2 ), suggesting that annual adjustments of xylem structure follow a safety–efficiency trade-off. The acute drought plunged hydraulic efficiency across all treatments. The combination of acute and prolonged drought resulted in vulnerable and inefficient new xylem, disrupting the stability of the anatomical trade-off observed in the rest of the years. The xylem hydraulic traits showed no consistent direct link to ΨL, pd . In the future, changes in seasonality of soil and atmospheric moisture are likely to have a critical impact on the ability of P. edulis to acclimate its xylem to warmer climate. Furthermore, the increasing frequency of acute droughts might reduce hydraulic resilience of P. edulis by repeatedly creating vulnerable and less efficient anatomical structure.